The Role of Visual Communication in Representing Green Mobility in Electric Car Marketing Advertisements through Semiotic Analysis - Ferrari, Raden Muhammad Luthfi; Ilham, Yanuar; Ulum, Muhammad Agung Bachrul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research explores the representation of green mobility in electric vehicle advertisements from Wuling and Hyundai in Indonesia, utilizing a semiotic analysis based on Roland Barthes' theory. The study examines how denotative, connotative, and mythological elements in the advertisements contribute to shaping public perceptions of electric vehicles as symbols of sustainability and modern lifestyle. By analyzing visual and verbal signs, such as the use of green colors, futuristic designs, and slogans like “Drive for a Green Life” and “Power Up the Future,” the study reveals how electric vehicles are portrayed not only as eco-friendly alternatives but also as lifestyle choices for the urban class. The findings suggest that these advertisements construct electric vehicles as part of a broader narrative about social transformation and environmental consciousness. This research contributes to the understanding of how semiotic theory can be applied to product advertising, offering insights into the role of visual communication in promoting sustainable lifestyles.